Konfederacja barska - Konopczynski, Wladyslaw (Warszawa : Volumen, 1991)
A history of the unrest in Poland during the Partitions of the 18th century.
Vol. 2 contains index.
Includes bibliographical references.
Keywords: Barska konfederacja; Poland -- History -- Partition period, 1763-1796.